A new species of Polyosma (Escalloniaceae / Polyosmaceae) from Thailand and new synonyms - Esser, Hajo; Saw, Leng Guan (Phytotaxa, 2015)
Polyosma pilosa sp. nov. is described as a new species from Thailand. Polyosma arguta, P. bracteolata, P. elongata, and P. oblonga are proposed as new synonyms of other Thai species, and five species from Bangladesh, Indonesia and Thailand are lectotypified.